Wnt signaling pathway-related gene PRICKLE1 is a prognostic biomarker for esophageal squamous cell carcinoma - He, Jinxian; Liang, Gaofeng; Tian, Hui; Wang, Yiqing; Yu, Li; Lv, Wang; Hu, Jian; Shen, Weiyu (Frontiers in Oncology, 2023)
Esophageal squamous cell carcinoma (ESCC) has become a major health risk to human health. Although significant clinical progress has been made in the treatment of ESCC, the prognosis of patients still needs to be improved. Therefore, it is important to screen effective molecular indicators for the prognosis of ESCC. In this study, the intersection of up-regulated genes, down-regulated genes, and Wnt signaling pathway-related genes in ESCC was taken, and 47 overlapping genes were found. PRICKLE1 was determined to be an independent prognostic factor in ESCC based on univariate and multifactorial COX risk regression models. Kaplan-Meier survival curves showed that patients in the PRICKLE1 high expression group had significantly better overall survival. In addition, we performed various experiments to examine the effects of PRICKLE1 overexpression on proliferation, migration, and apoptosis of ESCC cells. The experimental results showed that the PRICKLE1-OE group had reduced cell viability, significantly lower migration ability and significantly higher apoptosis rate compared to the NC group.Therefore, we hypothesized that high PRICKLE1 expression could be used to predict the survival rate of ESCC patients, which could be used as an independent prognostic indicator for ESCC patients and provide potential applications for ESCC clinical treatment.